Current control of Z-source four-leg inverter for autonomous photovoltaic system based on model predictive control; Известия Томского политехнического университета [Известия ТПУ]. Инжиниринг георесурсов; Т. 332, № 7 - Boussabeur M. T. Mohamed; Rabhi B. Boualaga; Aboelsaud R. Raef; Ibrahim Ahmed I. M. Ibrahim Mohamed; Toumi D. Djaafar; Zellouma L. Laid; Garganeev A. G. Alexander Georgievich (2021, 2021)
Заглавие с титульного листа